Retoryka map politycznych. Spory terytorialne w kontekście geoinformacyjnym - Miłkowska, Natalia (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Geoinformation Science in the twenty-first century has become an integral part of our lives. GPS navigation, exploration of cities via Street View or GeoTagging are just a few examples of modern cartography. In China, access to spatial data as well as to media reports is a subject to government control. Presented maps thus reflect a vision of the world seen through the eyes of the CCP. New law not only gives great opportunities for development of Chinese GIS, but also outlines the borders of the country, illustrating the political aspirations of the Middle Kingdom.